Monitors vs. Smart Glasses: A Study on Cognitive Workload of Digital Information Systems on Forklift Trucks - Gross, Benno; Bretschneider-Hagemes, Michael; Stefan, Andreas; Rissler, Jörg (Digital Human Modeling. Applications in Health, Safety, Ergonomics, and Risk Management, 2018)
New digital work equipment is increasingly affecting the approach to work. They enable more efficient, mobile and flexible operation, at the same time, however, new potential hazards and risks may arise for employees. A number of digital devices and their corresponding application context have not yet been comprehensively researched in the field of occupational sciences. In order to be able to recognize potential hazards in a preventive approach, this study examines the impact of the use of such devices in the context of forklift trucks on the safety and health of employees. In particular, the use of two types of smart glasses and of a monitor has been investigated. For the assessment of cognitive workload, the study made use of a standardized reaction test procedure, the Detection Response Task (DRT) according to ISO 17488 as well as subjective assessment using the NASA Task Load Index (NASA-TLX). This research will provide valuable information about possible work related hazards regarding the use of smart glasses on forklift trucks with respect to cognitive workload.